Gymnastics coaching and science: bionechanics perspectives - Toledo, E. de; Fernandes Antualpa, K. (High performance gymnastics, 2014)
This paper has examined some in gymnastics research (coaching of the major contemporary issues biomechanics interface, complex skills analysis, and skill development and learning). The paper started with an overview of the coaching biomechanics interface and highlighted how this can be used to build a conceptual link between biomechanics and coaching knowledge. The area of complex skill analysis was discussed which provided insights into the link between similar skills and how more complex skills emerge naturally as gymnasts and coaches seek to optimise performance. Finally the issues surrounding skill development and learning are introduced to explain how this interesting and relevant theoretical area can inform coaches decisions. The application of these scientific principles form the future of gymnastics coaching.